Pengaruh Disiplin Dan Motivasi Terhadap Kinerja Pegawai Pada Kantor Kecamatan Ciseeng Kabupaten Bogor - Siti Holisoh; Suprapto Suprapto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract- This study aims to determine the effect of work discipline and motivation on employee performance at the Ciseeng District Office. Discipline and motivation are two important factors influencing employee performance in providing optimal public services. The method used was quantitative with an associative approach. The sample in this study consisted of 61 employees. Data were collected through questionnaires and analyzed using validity and reliability tests, multiple linear regression, t-tests, and F-tests. The results of the analysis indicate that, partially, work discipline has a significant effect on employee performance, as does work motivation. Simultaneously, both variables have a significant effect on employee performance. Thus, improving discipline and motivation can improve employee performance at the Ciseeng District Office.